Visible-light-induced condensation cyclization to synthesize benzimidazoles using fluorescein as a photocatalyst. Issue 13 (3rd June 2019) - Li, Zhuofei; Song, He; Guo, Rui; Zuo, Minghui; Hou, Chuanfu; Sun, Shouneng; He, Xin; Sun, Zhizhong; Chu, Wenyi
Abstract : A mild strategy for visible-light-induced synthesis of benzimidazoles was developed using aromatic aldehydes and o -phenylenediamines as substrates. Abstract : A mild strategy for visible-light-induced synthesis of benzimidazoles was developed using aromatic aldehydes and o -phenylenediamines as substrates. The use of an organic dye, fluorescein, as an innoxious photocatalyst provided a mild and inexpensive catalytic system to synthesize a series of benzimidazoles in moderate to excellent yields. It was originally applied to this system to obtain benzimidazoles. Besides, the catalytic system does not require an additional oxidant or metal which was good for the environment.